Comparison between reconstituted sheep faeces and rumen fluid inocula and between in vitro and in sacco digestibility methods as predictors of intake and in vivo digestibility - Nsahlai, I.V.; Umunna, N.N. (Cambridge University Press, 1996)
This study (conducted in Debre Zeit, Ethiopia in 1993) examined (i) the effect of source of inoculum on in vitro dry matter (DM) digestibility (1VDMD) and gas production (GP) and (ii) the IVDMD, GP and in sacco degradability as predictors of in vivo DM digestibility (DMD) and intake. Six ruminally cannulated male sheep (used in the degradability studies and from which rumen fluid was harvested for the in vitro studies) and six intact sheep (from which faeces for reconstitution was obtained) were given teff straw ad libitum supplemented with 200 g/day of concentrate (1:1 mixture of noug (Guizotia abyssinica) cake and wheat middlings). In determining IVDMD on 26 feeds, pepsin-HC1 digestion was replaced with neutral detergent extraction. Microbial GP was measured on these feeds incubated with rumen fluid or reconstituted faeces inocula at various time periods. The degradability of each feed was determined by the nylon bag technique in three sheep. Eighty-eight intact male Ethiopian Menz type sheep (mean liveweight 256 (S.D. = 1·98) kg) were used in a randomized complete block experiment to determine intake and digestibility.